Pengaruh Demografi, Status Ekonomi Keluarga, Pola Makan, Jenis Makan dan Cara Penyajian terhadap Kejadian Stunting - Wastini Wastini; Sobar Darmaja; Istiana Kusumastuti (Poltekkes Kemenkes Padang, 2025)
Stunting is a condition of growth failure in children under five caused by chronic malnutrition, resulting in height that is not in accordance with their age. This condition reflects prolonged inadequate nutrient intake, making adequate nutrition from an early age highly important. The family’s economic status plays a major role in determining the quality of food consumption. Improving the quality and quantity of food consumed by toddlers can have a positive impact on their growth and development. This study aimed to analyze the influence of demographic factors, family economic status, dietary patterns, types of food, and food presentation methods on the incidence of stunting among children aged 12–59 months. The research employed an analytical correlational design with a cross-sectional approach, involving parents of children aged 24–59 months. Data were collected using questionnaires covering information on economic status and feeding practices, and analyzed using a simple logistic regression test. The results showed that stunting is influenced by various interrelated factors, particularly demographic conditions, family economic status, and the patterns and quality of food intake. In conclusion, improvements in these factors can reduce stunting incidence. It is recommended to enhance nutrition education, expand access to healthcare services, provide family support, and offer nutritious and appealing food for toddlers.